Molecular genetic techniques in current biomedical research. Part II: PCR applications in diagnostics of human infectious diseases - A. N. Volkov; L. V. Nacheva; Yu. V. Zakharova (Фундаментальная и клиническая медицина, 2021)
Polymerase chain reaction (PCR)-based diagnostics is currently established as a gold standard for the detection of microorganisms. The features of PCR include rapid amplification of DNA and RNA as well as high sensitivity and specificity. In contrast to diagnostic microbiology, PCR diagnostics does not require preliminary culture of the microorganisms for their identification, reducing both time and costs of the diagnostic procedure. The lecture discusses the molecular basis behind the modern technical solutions for the PCR diagnostics of human infectious diseases including multiplex and reverse transcription PCR. We describe the principles of qualitative and quantitative PCR-based detection of pathogens in biological samples and provide the examples of PCR application for solving specific diagnostic scenarios. The lecture is primarily designed for students of biomedical specialties and healthcare professionals using molecular genetic techniques in their practice.